SEJARAH PERKEMBANGAN ADVOKAT UNTUK MENEGAKKAN KEADILAN DI INDONESIA - Lubis, Fauziah; Fahrol, Muhammad; Harahap, Ongku; Diningsih, Suriani; Harahap, Juita Sari; Hanifah, Abu; Hasibuan, Sahrial (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The history of the development of the advocate profession in Indonesia reflects the long journey in realizing an independent and just justice system. During the colonial period, the profession of advocate was limited by discriminatory regulations, only allowing advocates of European nationality or those with approval from the colonial government. After independence, the regulation of advocates underwent reform through several laws aimed at establishing an advocate profession that was independent and had integrity. The peak was the birth of Law Number 18 of 2003 concerning Advocates, which established advocacy as a profession that is free, independent and not bound by government power. Through this law, the role of advocates as law enforcers on a par with prosecutors, judges and police is increasingly strengthened. This article aims to provide a chronological overview of the development of the advocate profession in Indonesia, the challenges faced, and its implementation in the modern justice system. With a historical and analytical approach, this research shows that the development of the advocate profession not only reflects the dynamics of law in Indonesia, but also efforts to ensure access to justice for all levels of society